Early Spontaneous Abortion in Fresh- and Frozen-Embryo Transfers: An Analysis of Over 35,000 Transfer Cycles - Shuai, Jun; Chen, Qiao-li; Chen, Wen-hong; Liu, Wei-wei; Huang, Guo-ning; Ye, Hong (Frontiers in Endocrinology, 2022)
Abstract Background: The aim of this study was to explore the risk factors for early spontaneous abortion (ESA) in fresh- and frozen-embryo transfers. Methods: This retrospective cohort study comprised a total of 35,076 patients, including 15,557 women in the fresh-embryo transfer group and 19,519 women in the frozen-embryo transfer group from January 2016 to December 2020. The primary outcome of this study was ESA, which we defined as the termination of embryonic development before 12 weeks of pregnancy (i.e., an early abortion after artificial multi-fetal pregnancy reduction was excluded). Results: In the 35,076 ART transfer cycles, the incidence of ESA was 5.77% (2023/35,076), and the incidence rates for ESA in fresh and frozen cycles were 4.93% (767 of 15,557) and 6.43% (1,256 of 19,519), respectively. Using a multivariate logistic regression analysis model, maternal age, body mass index (BMI), and number of embryos transferred were independent predictors for ESA. In addition, frozen-thawed transfer was a risk factor for ESA as compared with fresh transfer (OR = 1.207; 95% CI, 1.094–1.331; P = 0.000), blastocyst transfer was risk factor for ESA as compared with cleavage transfer (OR =1.373; 95% CI, 1.186–1.591; P = 0.000 in the total group; OR = 1.291; 95% CI, 1.111–1.499; P = 0.001 in the frozen-transfer group), and unexplained infertility was a protective factor for ESA only in the frozen group (OR = 0.746; 95% CI, 0.565–0.984; P = 0.038). Conclusions: Maternal age, BMI, number of embryos transferred, and frozen-thawed transfer were independent risk factors for ESA in assisted reproductive technology treatment cycles.